Cervical cancer risk in HPV‐positive women after a negative FAM19A4/mir124‐2 methylation test: A post hoc analysis in the POBASCAM trial with 14 year follow‐up - De Strooper, Lise M.A. (Int J Cancer, 2018)
DNA methylation analysis of cervical scrapes using FAM19A4 and mir124‐2 genes has shown a good clinical performance in detecting cervical cancer and advanced CIN lesions in need of treatment in HPV‐positive women. To date, longitudinal data on the cancer risk of methylation test‐negative women are lacking. In our study, we assessed the longitudinal outcome of FAM19A4/mir124‐2 methylation analysis in an HPV‐positive screening cohort with 14 years of follow‐up. Archived HPV‐positive cervical scrapes of 1,040 women (age 29–61 years), who were enrolled in the POBASCAM screening trial (ISRCTN20781131) were tested for FAM19A4/mir124‐2 methylation. By linkage with the nationwide network and registry of histo‐ and cytopathology in the Netherlands (PALGA), 35 cervical cancers were identified during 14 years of follow‐up comprising three screens (baseline, and after 5 and 10 years). The baseline scrape of 36.1% (n = 375) women tested positive for FAM19A4/mir124‐2 methylation, including 24 women with cervical cancer in follow‐up, and 30.6% (n = 318) had abnormal cytology (threshold borderline dyskaryosis or ASCUS), including 14 women with cervical cancer in follow‐up. Within screening round capability of FAM19A4/mir124‐2 methylation to detect cervical cancer was 100% (11/11, 95% CI: 71.5–100). Kaplan–Meier estimate of 14‐year cumulative cervical cancer incidence was 1.7% (95% CI: 0.66–3.0) among baseline methylation‐negative and 2.4% (95% CI: 1.4–3.6) among baseline cytology‐negative women (risk difference: 0.71% [95% CI: 0.16–1.4]). In conclusion, a negative FAM19A4/mir124‐2 methylation test provides a low cervical cancer risk in HPV‐positive women of 30 years and older. FAM19A4/mir124‐2 methylation testing merits consideration as an objective triage test in HPV‐based cervical screening programs.